Pengaruh Kepemilikan Manajerial dan Hubungan Sosial CEO dengan Komisaris Independen terhadap Manajemen Laba: Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2019 - 2023 - Putri, Azizah Dwi; Nelvirita, Nelvirita; Fawziah, Intan Nurbaiti (Jurnal Eksplorasi Akuntansi, 2025)
This study aims to examine the effect of managerial ownership and CEO social relations with Independent Commissioners on earnings management in manufacturing companies listed on the Indonesia Stock Exchange for the period 2019-2023. Using a purposive sampling technique, a sample of 38 companies was obtained. Earnings management is measured using the Modified Jones Model, managerial ownership is measured by the percentage of management share ownership of outstanding shares, and social relations are measured using the Social Network Index (SNI). Multiple linear regression analysis with SPSS version 26 shows that the independent variables simultaneously affect the dependent variable. Partially, managerial ownership has no significant effect on earnings management, while CEO social relations with Independent Commissioners have a significant positive effect on earnings management. The implications of this study emphasize the importance of strengthening regulations related to commissioner independence, especially in terms of social relations, and encouraging investors to consider social relations factors in investment analysis. The limitations of the study include the sample period covering the pandemic and focusing on the manufacturing sector, while further research can expand the scope of the industrial sector and develop more comprehensive social relations measurement metrics.